Las estrategias metodológicas y su incidencia en la calidad de la educación en los procesos de admisión y nivelación de la Universidad Técnica Estatal de Quevedo, en el período 2020-2021 - Muñoz Mazacon, Noraya Marieli (2022)
Social demands, current education trends, and the professional profile that globalization is requiring, new emerging forms of professionalization and acquisition of skills and competencies for professional performance towards personal fulfillment and social contribution; they demand an urgent review of the conditions in which educational praxis is developing. Even more so when the scenario in which the educational fact is fulfilled is virtuality, we see that the methodological strategies of face-to-face education are insufficient and, in some cases, inadequate. The objective of this research is to establish the impact that the methodological strategies have in relation to the development of the training process of the Admission and Leveling Unit, for this, in the first place, it must be clarified which are the strategies that are developed, from a researcher's perspective yes, but based on the interpretation of the responses of students and teachers. Second, it is intended to establish the urgent methodological difficulties that must be faced in the pursuit of quality education. Finally, there will be a tour of the main methodological strategies that are in force, and that should be incorporated into the educational practice of this virtual modality in leveling. We will use a qualitative-quantitative methodology and data association, qualitative to the extent of interpreting the processes, qualifying them in their incidence for the research and relating them to the previous literature and research, quantitative because we will be making statistical interpretations related to data that will be collected and of association of data because the tabulation and interpretation of data will culminate in an interpretive analysis of the responses obtained.